Rainfall Variability Index (RVI) analysis of dry spells in Malaysia - Huang Y.F.; Ahmed A.N.; Ng J.L.; Tan K.W.; Kumar P.; El-Shafie A. (Springer Science and Business Media B.V., 2023)
annual variation; drought; frequency analysis; rainfall; spatial analysis; spatial distribution; Malaysia